If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5(x + 2) = 34 Reorder the terms: 3x + 5(2 + x) = 34 3x + (2 * 5 + x * 5) = 34 3x + (10 + 5x) = 34 Reorder the terms: 10 + 3x + 5x = 34 Combine like terms: 3x + 5x = 8x 10 + 8x = 34 Solving 10 + 8x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 8x = 34 + -10 Combine like terms: 10 + -10 = 0 0 + 8x = 34 + -10 8x = 34 + -10 Combine like terms: 34 + -10 = 24 8x = 24 Divide each side by '8'. x = 3 Simplifying x = 3
| 7*(13-6)=49 | | 5(6+m)=-3m+4(2M-5) | | -2(5s-6)-12=-3(6s+4)-5 | | 3x-1=(4) | | 29(c+27)=899 | | -(2x+5)=3(3x-2)-10 | | 16=-2b+7b | | 2+9x=10+15x | | 7*x-6=49 | | p-18.9=-7.8 | | 16-15t-20=-16+88 | | An=a+(n+-1)(d) | | -6-9m-m+3n= | | 3x-1=(2) | | -26=10n-6 | | 5(x-2)=3x+12 | | (x-1)(5x+8)(x+6)(x-10)=0 | | 3(1-8n)=-2(n-8) | | -2x^2+12x-2=0 | | (71+30)x=350+30x | | [8+3c]-11=-10 | | 6.8-2x=-10.2 | | 4.3+20=5.3+9 | | 8g-(4g)= | | -26(t-957)=-182 | | 7r^3-2r^2-21r-2=0 | | (X+2)+(2x+2)-2=x+4x | | -x^2+3=2x-1 | | 4x^6-9x^4+5x^2-1=0 | | p=2x+5+4x-3 | | (2x+3)-49=0 | | 9+4X=8X+12 |